Biofouling Mitigation Approaches during Water Recovery from Fermented Broth via Forward Osmosis - Stavros Kalafatakis; Agata Zarebska; Lene Lange; Claus Hélix-Nielsen; Ioannis V. Skiadas; Hariklia N. Gavala (Membranes, 2020)
Forward Osmosis (FO) is a promising technology that can offer sustainable solutions in the biorefinery wastewater and desalination fields, via low energy water recovery. However, microbial biomass and organic matter accumulation on membrane surfaces can hinder the water recovery and potentially lead to total membrane blockage. Biofouling development is a rather complex process and can be affected by several factors such as nutrient availability, chemical composition of the solutions, and hydrodynamic conditions. Therefore, operational parameters like cross-flow velocity and pH of the filtration solution have been proposed as effective biofouling mitigation strategies. Nevertheless, most of the studies have been conducted with the use of rather simple solutions. As a result, biofouling mitigation practices based on such studies might not be as effective when applying complex industrial mixtures. In the present study, the effect of cross-flow velocity, pH, and cell concentration of the feed solution was investigated, with the use of complex solutions during FO separation. Specifically, fermentation effluent and crude glycerol were used as a feed and draw solution, respectively, with the purpose of recirculating water by using FO alone. The effect of the abovementioned parameters on (i) ATP accumulation, (ii) organic foulant deposition, (iii) total water recovery, (iv) reverse glycerol flux, and (v) process butanol rejection has been studied. The main findings of the present study suggest that significant reduction of biofouling can be achieved as a combined effect of high-cross flow velocity and low feed solution pH. Furthermore, cell removal from the feed solution prior filtration may further assist the reduction of membrane blockage. These results may shed light on the challenging, but promising field of FO process dealing with complex industrial solutions.